2019
DOI: 10.1111/jan.14084
|View full text |Cite
|
Sign up to set email alerts
|

Helping hospitalized smokers in Hong Kong quit smoking by understanding their risk perception, behaviour, and attitudes related to smoking

Abstract: Aim: To understand the risk perceptions, behaviour, attitudes, and experiences related to smoking among hospitalized Chinese smokers.Background: Understanding hospitalized smokers' perceptions of risks associated with smoking, along with their behaviour, attitudes, and smoking-related experiences, is essential prerequisite to design effective interventions to help them quit smoking.Design: A phenomenological research design was adopted. Results: Four themes were generated: (a) associations between perception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 51 publications
1
18
0
2
Order By: Relevance
“…We successfully achieved data saturation after recruiting and interviewing 44 respondents who were self-reported to exhibit solitary drinking behaviour. The current sample size was comparable to other descriptive phenomenological studies on addictive behaviours [ 23 , 24 , 25 ]. Of the respondents, 72.7% (n = 32) participated the interviews face-to-face, and the remaining opted to participate via online.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…We successfully achieved data saturation after recruiting and interviewing 44 respondents who were self-reported to exhibit solitary drinking behaviour. The current sample size was comparable to other descriptive phenomenological studies on addictive behaviours [ 23 , 24 , 25 ]. Of the respondents, 72.7% (n = 32) participated the interviews face-to-face, and the remaining opted to participate via online.…”
Section: Resultssupporting
confidence: 70%
“…We suggest that future studies examine the role of the identified factors in this qualitative study, including enhancement and coping drinking motives, social discomfort, reduced self-control, automatic mental processes, and desperate reactions to stressors using a quantitative approach, and determine how these factors relate to solitary drinking among adolescents and young adults by controlling the confounders, such as socioeconomic factors via different statistical methods, such as linear or logistic regression. This sequential approach is also commonly adopted in the field of addictive behaviours [ 23 , 24 , 25 , 52 , 53 ]. Fifth, age would influence our respondents’ responses in the semi-structured interviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, assisting people to engage in healthy lifestyle practices, such as quitting smoking, avoiding excessive alcohol use, maintaining a balanced diet and engaging in regular physical activity, can help prevent NCDs and improve the overall health of the population. However, despite their awareness of the associated health hazards, many people lack motivation or find it difficult to modify their health-risk behaviors, especially when there is little advice and support from healthcare professionals [ 7 , 8 , 9 , 10 ]. In addition, health-risk behaviors co-occur in clusters, such that many people engage in multiple behaviors [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, assisting people to engage in healthy lifestyle practices, such as quitting smoking, avoiding excessive alcohol use, maintaining a balanced diet and engaging in regular physical activity, can help prevent NCDs and improve the overall health of the population. However, despite their awareness of the associated health hazards, many people lack motivation or nd it di cult to modify their health-risk behaviours, especially when there is little advice and support from healthcare professionals [7][8][9][10]. In addition, health-risk behaviours co-occur in clusters, such that many people engage in multiple behaviours [11][12][13].…”
Section: Introductionmentioning
confidence: 99%